Retention of virulence following adaptation to colistin in Acinetobacter baumannii reflects the mechanism of resistance. (22nd April 2015) - Wand, Matthew E.; Bock, Lucy J.; Bonney, Laura C.; Sutton, J. Mark
Abstract: Objectives: Colistin resistance in Acinetobacter baumannii has been associated with loss of virulence and a negative impact on isolate selection. In this study, exposure of clinical isolates to suboptimal concentrations of colistin was used to explore the capacity to develop resistance by diverse mechanisms, and whether acquired resistance always reduces fitness and virulence. Methods: Twelve colistin-susceptible clinical A. baumannii isolates were exposed to a sub-MIC concentration of colistin over 6 weeks with weekly increases in concentration. Stable resistance was then phenotypically investigated with respect to antibiotic/biocide resistance, virulence in Galleria mellonella and growth rate. Putative mechanisms of resistance were identified by targeted sequencing of known resistance loci. Results: Eight A. baumannii isolates acquired resistance to colistin within 1 week with MICs ranging from 2 to >512 mg/L. By 6 weeks 11 isolates were resistant to colistin; this was linked to the development of mutations in pmr or lpx genes. Strains that developed mutations in lpxACD showed a loss of virulence and increased susceptibility to several antibiotics/disinfectants tested. Two of the colistin-resistant strains with mutations in pmrB retained similar virulence levels to their respective parental strains in G. mellonella . Conclusions: Acquisition of colistin resistance does not always lead to a loss of virulence, especially when this is linked to mutations in pmrB . This underlines the importance of understanding the mechanism of colistin resistance as well as the phenotype.